2013
DOI: 10.1016/j.bbamem.2013.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Probing the interaction of Arg9Cys mutated phospholamban with phospholipid bilayers by solid-state NMR spectroscopy

Abstract: Phospholamban (PLB) is a 52 amino acid integral membrane protein that interacts with the sarcoplasmic reticulum Ca2+ ATPase (SERCA) and helps to regulate Ca2+ flow. PLB inhibits SERCA impairing Ca2+ translocation. The inhibition can be relieved upon phosphorylation of PLB. The Arg9 to Cys (R9C) mutation is a loss of function mutation with reduced inhibitory potency. The effect R9C PLB has on the membrane surface and the hydrophobic region dynamics was investigated by 31P and 2H solid-state NMR spectroscopy in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 61 publications
(90 reference statements)
1
11
0
Order By: Relevance
“… 49 Both P-PLB and R9C-PLB have significantly less interaction with the membrane. 26 , 49 Therefore, interaction with lipids may be involved in regulating PLB function. WT-PLB is dominated by the pentamer form.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 49 Both P-PLB and R9C-PLB have significantly less interaction with the membrane. 26 , 49 Therefore, interaction with lipids may be involved in regulating PLB function. WT-PLB is dominated by the pentamer form.…”
Section: Resultsmentioning
confidence: 99%
“…However, 2 H NMR spectra investigating lipid acyl chain dynamics do not show any effect upon R9C-PLB or P-PLB addition. 26 More likely, the secondary structure change occurs upon R9C mutation or phosphorylation. Unwinding is observed at Ala24 in domain Ib, suggesting a population shift from the dominant folded state toward an unfolded state.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A, schematic representation of primary sequence of WT-PLB and the mutant PLB constructs. The amino acid sequence of the PLB protomer shows the N-terminal cytosolic domain Ia (residues 1-16), flexible linker (residues 17-22), domain Ib (residues [23][24][25][26][27][28][29][30], and the C-terminal transmembrane domain II (residues 31-52). Cer or YFP was fused to the N terminus.…”
Section: R9c-plb Exerts a Positive Inotropic And Positive Lusitropicmentioning
confidence: 99%
“…Proposed mechanisms include trapping of PKA (8), disruption of PLB phosphorylation (8,9,20,21), and loss of PLB inhibitory function (8, 9, 20 -22). Other studies have suggested that the R9C mutation mimics PLB phosphorylation by partial unfolding of the cytoplasmic helix resulting in decreased helical conformation (23) or detachment of PLB cytoplasmic domain from the membrane surface (24,25). Moreover, we have previ-ously proposed that the R9C mutation induces oxidation-dependent cross-linking of adjacent R9C-PLB protomers (20).…”
mentioning
confidence: 99%